Sinusoidal Obstruction Syndrome Following Myeloablative Therapy and Tranexamic Acid Treatment for Hemorrhage in Two Patients with Neuroblastoma - Felix Zirngibl; Carina Flemmig; Peter Lang; Annette Künkele; Angelika Eggert; Johannes H. Schulte; Hedwig E. Deubzer (MDPI AG, 2020)
Adverse thromboembolic events following administration of the anti-fibrinolytic agent tranexamic acid (TA), used to prevent/treat excessive blood loss, are rare. We present the clinical course of two young patients (22 and 56 months) receiving busulfan/melphalan (Bu/Mel) high-dose chemotherapy with autologous hematopoietic stem cell transplantation (HSCT) to treat high-risk neuroblastoma, who developed hepatic sinusoidal obstruction syndrome (SOS) within 48 h after systemic TA treatment for a hemodynamically relevant hemorrhage. Defibrotide treatment resolved hepatic SOS, but the short time between TA administration and SOS onset suggests a causal association.